2008
DOI: 10.1002/cjoc.200890017
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Catalyzed One‐pot Synthesis of 3,4‐Dihydroquinazolin‐4‐ones from Anthranilic Acids, Ortho Esters and Amines under Solvent‐free Conditions

Abstract: A simple and efficient procedure has been developed for the one-pot synthesis of 3,4-dihydroquinazolin-4-ones from anthranilic acids, ortho esters and amines using a catalytic amount of iodine under solvent-free conditions to afford the corresponding products in excellent yields. The direct use of commercially available catalyst, mild and solvent-free reaction conditions, short reaction time, easy workup and excellent yields are the advantages of the present protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Meanwhile, iodine has emerged as a very efficient Lewis acid catalyst for various organic transformations and is relatively inexpensive compared to other Lewis acids, including rare earth metal triflates, and is more tolerant in comparison to typical Lewis acids/bases [38][39][40]. Furthermore, Zahouily et al showed that iodine supported on natural phosphate could be effectively employed for the protection of carbonyl compounds as their thioacetals in good yield at ambient temperature and mild conditions [41].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, iodine has emerged as a very efficient Lewis acid catalyst for various organic transformations and is relatively inexpensive compared to other Lewis acids, including rare earth metal triflates, and is more tolerant in comparison to typical Lewis acids/bases [38][39][40]. Furthermore, Zahouily et al showed that iodine supported on natural phosphate could be effectively employed for the protection of carbonyl compounds as their thioacetals in good yield at ambient temperature and mild conditions [41].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported several molecular iodine-catalysed organic reactions. [19][20][21] In continuation of our investigations on iodine catalysed reactions, we now report an efficient procedure for the synthesis of symmetrical bisamides from aldehydes and amides in the presence of a catalytic amount of molecular iodine under neutral conditions (Scheme 1).…”
mentioning
confidence: 97%
“…(3,-4(3H)-quinazolinone (4j)[5] White solid.1 H NMR (CDCl 3 ) δ = 8.35 (d, J = 7.8 Hz, 1H), 8.07 (s, 1H), 7.84-7.81 (m, 1H), 7.77 (d, J = 7.9 Hz, 1H), 7.63 (d, J = 8.5 Hz, 1H), 7.59-7.56 (m, 2H), 7.31 (dd, J = 8.5, 2.2 Hz, 1H). 13 C MR (CDCl 3 ) δ = 160.5, 147.8, 145.1, 136.7, 135.0, 133.8, 131.4, 129.3, 128.1, 127.9, 127.3, 126.5, 122.2.…”
mentioning
confidence: 99%